A conceptual exploration on the synergistic anti-tumor effects of high-order combination of OHSV2-DSTEFAP5/CD3, CAR-T cells, and immunotoxins in hepatocellular carcinoma - Dong, Shuang; Chen, Xin; Li, Xiaoyu; Wang, Yang; Huang, Qing; Li, Yuanxiang; Jin, Jing; Zhu, Xianmin; Zhong, Yi; Cai, Qian; Xue, Chang; Guo, Fang; et al. (Frontiers in Immunology, 2025)
BackgroundAlthough the treatment landscape for advanced hepatocellular carcinoma (HCC) has seen significant advancements in the past decade with the introduction of immune checkpoint inhibitors and antiangiogenic drugs, progress has fallen short of expectations. Recently, a novel engineered oncolytic virus (OHSV2) that secretes dual-specific T-cell engagers (DSTEs) targeting the fibroblast activation protein (FAP) was developed and combined with GPC3-targeting CAR-T cells and immunotoxins to exert a synergistic antitumor effect.MethodsOHSV2-DSTEFAP5/CD3 was initially generated by transducing the DSTEs engaging FAP5 on fibroblasts into the backbone of our oncolytic virus OHSV2. An innovative high-order combination was devised in a xenograft mouse model to conceptually explore whether enhanced anti-tumor effects could be achieved. Additionally, the underlying mechanisms of synergistic effects and safety profiles were preliminarily investigated.ResultsOHSV2-DSTEFAP5/CD3 effectively targeted and eliminated fibroblasts in vitro while maintaining cytotoxicity and inducing immune activation compared to parental OHSV2. In vivo, dose-adjusted combination therapy resulted in a remarkable antitumor effect compared to control treatments, leading to tumor regression in 40% of mice without significant toxicity to major organs. Mechanistically, rather than directly depleting fibroblasts, OHSV2-DSTEFAP5/CD3 played an essential role in priming T-cell proliferation, infiltration, and activation, and inhibiting the supportive interaction between cancer cells and fibroblasts.ConclusionsThis high-order combination represents a novel multiple-wave immunotherapeutic approach for HCC. Despite being a conceptual exploration, this strategy has demonstrated promising therapeutic efficacy and acceptable safety profiles.